Prenatal Alcohol Exposure: Profiling Developmental DNA Methylation Patterns in Central and Peripheral Tissues - Lussier, Alexandre A.; Bodnar, Tamara S.; Mingay, Matthew; Morin, Alexandre M.; Hirst, Martin; Kobor, Michael S.; Weinberg, Joanne (Frontiers in Genetics, 2018)
Prenatal alcohol exposure (PAE) alters the development of neurobiological systems, leading to lasting neuroendocrine, neuroimmune, and neurobehavioral deficits. Although the etiology of this reprogramming remains unknown, emerging evidence suggests DNA methylation as a potential mediator and biomarker for the effects of PAE due to its responsiveness to environmental cues and relative stability over time. Here, we utilized a rat model of PAE to examine the DNA methylation profiles of rat hypothalami and leukocytes at four time points during early development to assess the genome-wide impact of PAE on the epigenome and identify potential biomarkers of PAE. Hypothalami were analyzed on postnatal (P) days 1, 8, 15, 22 and leukocytes at P22 to compare central and peripheral markers. Genome-wide DNA methylation analysis was performed by methylated DNA immunoprecipitation followed by next-generation sequencing. PAE resulted in lasting changes to DNA methylation profiles across all four ages, and a large number of differentially methylated regions (DMRs) displayed the same direction of change in the hypothalamus and leukocytes of P22 pups. The majority of these DMRs were located in intergenic regions, which contained several computationally-predicted transcription factor binding sites. Differentially methylated genes were generally involved in immune function, epigenetic remodelling, metabolism, and hormonal signaling. Persistent DNA methylation changes in the hypothalamus may be associated with the long-term deficits observed in PAE. Furthermore, correlations between epigenetic alterations in peripheral tissues and those in the brain will provide a foundation for the development of biomarkers of fetal alcohol spectrum disorder (FASD).